Using Learning Objectives when Teaching in Czech Primary Schools: Facts or Fiction? - Stará, Jana; Starý, Karel (Revija za elementarno izobraževanje, 2019)
The paper presents the findings of a multiple case study exploring the way primary school teachers work with learning objectives in social studies teaching. The study has shown that learning objectives do not occur in an explicit form in the Czech primary school teaching. While observing teaching and learning, implicit objectives did emerge – in the beginnings of lessons, during the lesson in the process of solving learning tasks, and most of all, in the evaluatiion processes including the final reflection. In many lessons, there were differences between the learning objectives, teaching methods and evaluation of pupils’ learning.